Design of Physics Learning Module Integrated with Problem Based Learning Model on Renewable Energy Material Class X MA - Nindi Syakila; Hidayati, Hidayati (Journal of Innovative Physics Teaching, 2024)
Independent Curriculum provides flexibility to schools and teachers in designing learning. However, this flexibility causes differences in the allocation of learning time in some schools. In physics subjects, some Madrasah Aliyah have less time allocation per week compared to other schools, this causes students to need to be trained to learn independently. Meanwhile, Phase E physics learning outcomes require students to play an active role in providing problem solving. Therefore, a learning module integrated with the Problem-Based Learning (PBL) model is needed to support independent learning and train students' problem-solving skills. This study aims to produce a physics learning module integrated with a valid PBL model on renewable energy material for class X Madrasah Aliyah. This research uses the Research and Development (R&D) method with the 4D development model, which includes defining, designing, developing, and disseminating stages. The module validation results showed a value of 0.92 with a very valid category. This shows that the developed module has met the validity criteria and is suitable for use. The implication of this research is that the module can help students learn independently and train students to solve problems.